The Effect Of The Utaut3 Construct On The Interest Of MSMEs In Using The Bank Syariah Indonesia QRIS Payment System With Trust, And Ease Of Use As A Mediation Variable: Systematic Literature Review (SLR) With Bibliometrics - Prabu Nurdin; Budi Eko Soetjipto; Madziatul Churiyah (Economics and Business Journal (ECBIS), 2026)
The development of financial technology has encouraged the transformation of the digital payment system in Indonesia, one of which is through the implementation of the Quick Response Code Indonesian Standard (QRIS) developed by Bank Indonesia to integrate various QR code-based payment services. This payment system is expected to be able to improve transaction efficiency, speed up the payment process, and expand financial inclusion for Micro, Small, and Medium Enterprises (MSMEs). However, the adoption rate of digital payment technology in the MSME sector still faces various challenges, both related to technological aspects, user psychological factors, and the influence of the social environment. This study aims to systematically examine the influence of constructs in the Unified Theory of Acceptance and Use of Technology (UTAUT3) on the interest of MSMEs in using the QRIS payment system at Bank Syariah Indonesia with trust and perceived ease of use as mediation variables. The research method used is Systematic Literature Review (SLR) with the PRISMA approach to identify, select, and analyze relevant scientific articles in the 2020–2025 period. The literature search process produced 2,395 articles from a database of reputable scientific journals, then an elimination process was carried out based on inclusion and exclusion criteria so that 71 articles were obtained that were eligible for further analysis. The study stages were carried out systematically through the process of identification, screening, feasibility assessment, and determination of final articles. The results of the study show that the main constructs in the technology acceptance model such as performance expectancy, effort expectancy, social influence, and facilitating conditions have an important influence on interest in using digital payment technology. In addition, additional factors such as trust and perceived ease of use have been proven to act as mediating variables that strengthen the relationship between technology construct and the intention to use QRIS by MSME actors. Trust in system security and ease of use of technology are crucial factors in increasing user confidence in digital payment services, especially in the context of Islamic banking-based financial services. The findings of this study provide a theoretical contribution to the development of a digital payment technology acceptance model based on UTAUT3 and provide practical implications for financial institutions and regulators in increasing the adoption of QRIS among MSME actors. The next research is suggested to develop an empirical model with a quantitative approach to test the relationship between variables more comprehensively in the context of the digital economy in Indonesia.